2011
DOI: 10.19030/cier.v4i2.4079
|View full text |Cite
|
Sign up to set email alerts
|

Problems Faced By Physical Handicapped Students In Educational Institutions In District Kohat

Abstract: The purpose of the study was to explore the problems faced by physical handicapped students in normal educational institutions and to find solutions to the problems faced by physical handicapped students. All the physical handicapped students studying in educational institutions in District Kohat constituted the population of the study. The study was delimited to the physical handicapped students studying in 20 general educational institutions at four levels; i.e., Elementary, Secondary, Higher Secondary and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…He revealed that despite the teachers of the visually impaired pupils giving the necessary attention, the schools do not have instructional materials for teaching them. This finding was corroborated by Hussain et al (2011) that the majority of the teachers gave special attention to them, but they do not have specific aids in the class room to teach them. According to Igune (2009), he also opined that most general teachers lacked the basic knowledge and skills to accommodate learners with visual impairment in the inclusive classrooms or even engage them in extra-curricular activities.…”
Section: Discussion Of the Findingsmentioning
confidence: 86%
“…He revealed that despite the teachers of the visually impaired pupils giving the necessary attention, the schools do not have instructional materials for teaching them. This finding was corroborated by Hussain et al (2011) that the majority of the teachers gave special attention to them, but they do not have specific aids in the class room to teach them. According to Igune (2009), he also opined that most general teachers lacked the basic knowledge and skills to accommodate learners with visual impairment in the inclusive classrooms or even engage them in extra-curricular activities.…”
Section: Discussion Of the Findingsmentioning
confidence: 86%